Decolonising Québec: Discursive Strategies in Michel Tremblay’s Mistero buffo - Dunnett, Jane (TTR, 1997)
AbstractDecolonising Québec : Discursive Strategies in Michel Tremblay 's Mistero buffo — During the 1960s and 1970s the concept of decolonisation was taken up by many Québécois intellectuals in their bid to promote the nationalist cause. Drawing on the theories of Albert Memmi and Frantz Fanon, such writers denounced what they regarded as the political, economic and cultural dependence of Québec. This article examines the way in which the topos of colonisation that permeated the social discourse of the period affected the translation and reception of Michel Tremblay's joual version of Mistero buffo. It seeks to demonstrate that Dario Fo's play has been transformed into a vehicle for challenging the perceived cultural imperialism of France and for asserting the importance of secularisation in the movement to "décolonise" Québec.